Policy approaches to grassland in planning documents of Ministry of Food Agriculture and Livestock in Turkey in the context of climate change - Dede I.; Serefoglu C. (New approaches for grassland research in a context of climate and socio-economic changes, 2012)
The grassland-based policy approaches are strongly linked with the livestock management be - cause the livestock nutrition system which is based on grazing intensively particularly on hilly and remote areas. This situation has been predominantly reflected in planning as the interventions directed to regulating the grazing intensity (over-grazing) and erosion control. The most comprehensive and concrete interventions for the establishment of policies for grassland in the context of impacts, mitigating and adapting to climate change have been seen in the Strategic Plan (2010-2014) and Performance Programmes. The needed re - sources for implementing the measures regarding grassland management and climate change accounts for 6.5% of total budget in Performance Programme 2012 showing significant increase of importance given to cli mate change when compared with the Performance Programme 2011. The measures regarding erosion control in IPARD Programme may be classified as the practices for mitigation purposes although it is not implied as a measure targeted to climate change in the Programme.
14. Meeting of the FAO-CIHEAM Subnetwork on Mediterranean Forages and Fodder Crops, 2012/10/03-06, Samsun (Turkey)